2014
DOI: 10.1002/2014jb011548
|View full text |Cite
|
Sign up to set email alerts
|

Low‐velocity zones along the San Jacinto Fault, Southern California, from body waves recorded in dense linear arrays

Abstract: We derive high-resolution information on low-velocity fault zone (FZ) structures along the San Jacinto Fault Zone (SJFZ), Southern California, using waveforms of local earthquakes that are recorded at multiple linear cross-fault arrays. We observe clear across-fault delays of direct P and S waves, indicating damage zones at different segments of the SJFZ. We then compute synthetic traveltimes and waveforms using generalized ray theory and perform forward modeling to constrain the FZ parameters. At the southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 53 publications
5
48
1
1
Order By: Relevance
“…13 and geological mapping near Hog Lake southeast of the array (Dor et al 2006). Stations at larger distance from the fault may record, in addition to the phases analysed in this work, also P and S body waves reflected within a low velocity fault zone layer (Yang et al 2014) and waves reflected from bimaterial fault interfaces to off-fault stations (Najdahmadi et al 2016). A recent deployment of a longer aperture array across the Clark fault at the same location of the BB array (Lin et al 2016) provides opportunities for analysing these and other signals indicative of the inner structure of the fault.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…13 and geological mapping near Hog Lake southeast of the array (Dor et al 2006). Stations at larger distance from the fault may record, in addition to the phases analysed in this work, also P and S body waves reflected within a low velocity fault zone layer (Yang et al 2014) and waves reflected from bimaterial fault interfaces to off-fault stations (Najdahmadi et al 2016). A recent deployment of a longer aperture array across the Clark fault at the same location of the BB array (Lin et al 2016) provides opportunities for analysing these and other signals indicative of the inner structure of the fault.…”
Section: Discussionmentioning
confidence: 65%
“…Internal structural components of the SJFZ have been studied using various seismic arrays that cross the fault at different locations (e.g. Li & Vernon 2001;Lewis et al 2005;Yang et al 2014;Ben-Zion et al 2015;Li et al 2015;Hillers et al 2016), along with geological mapping of rock damage and analysis of geomorphologic signals (Dor et al 2006;Wechsler et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) (Li et al 2007;Yang and Zhu 2010a;Yang et al 2011Yang et al , 2014). This technique not only uses measurements of travel-time delays of direct P and S waves, but also takes into account of the differential times between the direct and FZ-reflected P and S waves.…”
Section: Fz Wavesmentioning
confidence: 99%
“…Given these apparent limitations of FZTWs, other methods have potentially been more successful in determining the depth of fault zones. Refracted and reflected P-and S-waves can be used to infer the depth extent and properties of fault zones (Yang & Zhu 2010;Yang et al 2011Yang et al , 2014. These studies have demonstrated that the Calico and San Jacinto fault zones are shallow.…”
Section: Introductionmentioning
confidence: 99%